The influence of tightening regulations on patients with new psychoactive substance‐related disorders in Japan - Yuko Tanibuchi; Toshihiko Matsumoto; Daisuke Funada; Takuya Shimane (Wiley, 2018)
Abstract Aims This study aimed to investigate the influence of tightened regulations on new psychoactive substances in patients with disorders related to these drugs in Japan. Methods We used a biennial nationwide survey on drug‐related psychiatric disorders to examine why individuals who had previously used new psychoactive substances as their primary drug (the drug that had the greatest impact on their psychiatric symptoms) had switched to other drugs, how they had used drugs in the last 12 months and what type of drugs they were now using. We compared the clinical features of these individuals with patients who mainly used new psychoactive substances and had used these drugs at least once in the last 12 months. Results A total of 2262 people were included, and 399 had used new psychoactive substances. Of those, 71 people had switched to another drug as primary drug, mostly stimulant drugs (35.2%), hypnotics and anxiolytics (15.5%), and cannabis (14.1%) and used these drugs during the previous 12 months. The majority, 53.3%, had switched "because new psychoactive substances were no longer available." In total, 25 people mainly used new psychoactive substances. The group that had changed drugs had more experience of using methamphetamine and were more likely to have abused other drugs before using new psychoactive substances. They had often switched to illegal or prescription drugs after regulations had been tightened. Conclusion The number of patients abusing new psychoactive substances decreased after drug regulations were tightened, but new psychoactive substances‐related problems still exist. It is therefore not enough to tighten regulations. Drug dependence treatment and recovery support are also needed.